2007
DOI: 10.1128/jvi.01096-06
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus-Induced Resistance to Drugs That Activate the Mitotic Spindle Assembly Checkpoint in Burkitt's Lymphoma Cells

Abstract: Epstein-Barr virus (EBV)is associated with a number of human cancers, and latent EBV gene expression has been reported to interfere with cell cycle checkpoints and cell death pathways. Here we show that latent EBV can compromise the mitotic spindle assembly checkpoint and rescue Burkitt's lymphoma (BL)-derived cells from caspase-dependent cell death initiated in aberrant mitosis. This leads to unscheduled mitotic progression, resulting in polyploidy and multi-and/or micronucleation. The EBV latent genes respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 32 publications
1
55
0
Order By: Relevance
“…(d) Protein extracts from BL31 cells and BL31 cells infected with KO and revertant viruses were also subjected to western-blot analysis probing for expression of the anti-apoptotic factors (and targets of LMP-1), A20 and Bcl-2; g-tubulin was used as a loading control. EBNA3A and EBNA3C are both required for repression of Bim expression It was shown previously that latent infection of BL cells with EBV results in a significant reduction in the expression of the proapoptotic Bcl-2-family member, Bim (Clybouw et al, 2005;Leao et al, 2007). Moreover, this downregulation appears not to require expression of EBNA2 or the LMP proteins (Leao et al, 2007).…”
Section: Validation Of Recombinant Viruses In Bl31 Cellsmentioning
confidence: 99%
See 3 more Smart Citations
“…(d) Protein extracts from BL31 cells and BL31 cells infected with KO and revertant viruses were also subjected to western-blot analysis probing for expression of the anti-apoptotic factors (and targets of LMP-1), A20 and Bcl-2; g-tubulin was used as a loading control. EBNA3A and EBNA3C are both required for repression of Bim expression It was shown previously that latent infection of BL cells with EBV results in a significant reduction in the expression of the proapoptotic Bcl-2-family member, Bim (Clybouw et al, 2005;Leao et al, 2007). Moreover, this downregulation appears not to require expression of EBNA2 or the LMP proteins (Leao et al, 2007).…”
Section: Validation Of Recombinant Viruses In Bl31 Cellsmentioning
confidence: 99%
“…Analysis of EBV latent gene expression patterns in various EBV-positive BL-derived cell lines suggested that the EBNA3 family might play an important role in this survival phenotype. Correlation between survival and EBV-mediated repression of the BH3-only, Bcl-2-family member Bim (Bcl-2-interacting mediator of cell death) was also observed (Leao et al, 2007).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…The checkpoint-mediating proteins, Bub1, Cenp-F, BubR1, Bub3 and Mad2, are recruited to the kinetochore and stabilize the microtubule-kinetochore complex. It was shown earlier that EBV compromises the spindle assembly checkpoint and rescues BL cells from caspase-dependent cell death initiated by aberrant mitosis (Leao et al, 2007) but the mechanism was not explored. We have found that disruption of the mitotic checkpoint in EBNA-3C-expressing cells (Figure 5a) is associated with a dramatic decrease in BubR1 protein levels ( Figure 5b) and its transcriptional downregulation (Figure 5c).…”
Section: Genomic Instability In Ebv-infected Cellsmentioning
confidence: 99%